The European Spatial Development Perspective - Andreas Faludi (European Journal of Spatial Development, 2006)
The fact that they have created the European Union (EU) notwithstanding, Member States are suspicious of, and even hostile to it. This creates a dynamic that is often puzzling, and this is also true for spatial planning. The latter is not a competence of the European Community, but there is the inter-governmental European Spatial Development Perspective (ESDP) and INTERREG. Also, in this framework, the European Spatial Planning Observation Network (ESPON) has been set up with the purpose of providing an analytical base for following through on the ESDP agenda. Meanwhile, the Treaty establishing a Constitution for Europe has identified territorial cohesion as an objective of the Union and a competence shared with the Member States. While waiting for its ratification, the European Commission formulated its proposals for cohesion policy for 2007-2013. Against this backdrop, Member States resumed their initiative to give them a presence in a future territorial cohesion policy led by the Commission. In the changed circumstances after the French and Dutch ‘no’ to the Constitution, their ‘Territorial Agenda for the European Union’, due to be adopted in May 2007, will be even more significant. The Slovenian Presidency of 2008 may put this document before the European Council, which would be the first time that territorial issues had been discussed at this level.